Anomalous Origin of a Right Coronary Artery from Pulmonary Artery - Muhammad Shabbir Rawala; S. Tahira Shah Naqvi; Kinaan Farhan; Muhammad Yasin; Syed Bilal Rizvi (Case Reports in Cardiology)
Congenital defects of the coronary arteries are noted in 0.2–1.4% of the general population. The first case of an anomalous origin of right coronary artery from pulmonary artery (ARCAPA) was described by Brooks in 1885. ARCAPA has an overall incidence of 0.002% in the general population. Most of the cases are asymptomatic; however, it can lead to serious complications such as heart failure, ischemia, and sudden death. A 57-year-old man presented to the cardiologist’s office with complaints of shortness of breath and fatigue. The patient also had a previous history of coronary stents and heart failure. Initially, he was evaluated with a stress test which was reported as abnormal. The patient then underwent an invasive coronary angiography that revealed anomalous origin of the right coronary artery (RCA) and multivessel disease. Cardiothoracic surgery evaluated the patient and coronary artery bypass graft was performed. During the surgery, the anomalous origin of RCA from the pulmonary artery was identified and was successfully corrected by reimplanting the RCA into the ascending aorta. The anomalous origin of RCA is a rare yet life-threatening condition. The RCA due to its location of origin from the pulmonary artery tends to be a low-pressure vessel with a very thin and fragile wall. It also serves as a retrograde venous conduit from the left coronary circulation into the pulmonary artery. This connection results in a left-to-right shunt that explains the increase in oxygen saturation in the pulmonary artery and the high cardiac output which is normally seen in these cases. The clinical presentation can vary from coronary ischemia to heart failure or sudden death. Therefore, surgical correction is recommended even in asymptomatic patients. We present a case of an anomalous origin of RCA from the pulmonary artery which, unlike the origin of left coronary from pulmonary artery, is very rare. Patients with this condition should have early correction even if they are asymptomatic in order to prevent long-term complications.